Natural emissions under future climate condition and their effects on surface ozone in the Yangtze River Delta region, China. (February 2017) - Xie, Min; Shu, Lei; Wang, Ti-jian; Liu, Qian; Gao, Da; Li, Shu; Zhuang, Bing-liang; Han, Yong; Li, Meng-meng; Chen, Pu-long
Abstract: The natural emissions of ozone precursors (NOx and VOCs) are sensitive to climate. Future climate change can impact O3 concentrations by perturbing these emissions. To better estimate the variation of natural emissions under different climate conditions and understand its effect on surface O3, we model the present and the future air quality over the Yangtze River Delta (YRD) region by running different simulations with the aid of the WRF-CALGRID model system that contains a natural emission module. Firstly, we estimate the natural emissions at present and in IPCC A1B scenario. The results show that biogenic VOC emission and soil NOx emission over YRD in 2008 is 657 Gg C and 19.1 Gg N, respectively. According to climate change, these emissions in 2050 will increase by 25.5% and 11.5%, respectively. Secondly, the effects of future natural emissions and meteorology on surface O3 are investigated and compared. It is found that the variations in meteorological fields can significantly alter the spatial distribution of O3 over YRD, with the increases of 5–15 ppb in the north and the decreases of −5 to −15 ppb in the south. However, only approximately 20% of the surface O3 increases caused by climate change can be attributed to the natural emissions, with the highest increment up to 2.4 ppb. Finally, Ra (the ratio of impacts from NOx and VOCs on O3 formation) and H2 O2 /HNO3 (the ratio between the concentrations of H2 O2 and HNO3 ) are applied to study the O3 sensitivity in YRD. The results show that the transition value of H2 O2 /HNO3 will turn from 0.3 to 0.5 in 2008 to 0.4–0.8 in 2050. O3 formation in the YRD region will be insensitive to VOCs under future climate condition, implying more NOx need to be cut down. Our findings can help us understand O3 variation trend and put forward the reasonable and effective pollution control policies in these famous polluted areas. Highlights: The natural emissions of ozone precursors are sensitive to climate in YRD. BVOCs and soil NO emissions will increase by 25.5% and 11.5% in the future. Future natural emissions cause about 20% of the surface O3 increases, with the maximum of 2.4 ppb. O3 formation in YRD will be insensitive to VOCs in the future.